Conceptual Interface between Sensory Marketing and Impulsive Buying Behaviour of Millennials in South Africa - Ntobela , Thandazile Samukelisiwe; Mbukanma, Ifeanyi (The Journal of Accounting and Management, 2024)
Millennials in recent times has increase percentage participation in the retail market, which has been informed by diverse factors attributed to their socioeconomic exposures. It is also evident that the pattern of purchasing behaviour of millennials has its own consequences, which include buying out of their budget, making unplanned purchases, and even deviating from their fashion sense. These consequences engineered the objective of this study to systematically reveal the conceptual interface between sensory marketing and impulsive buying behaviour of millennials in South Africa. To achieve this objective, an exploratory literature review approach to research was employed, where information and deliberations on impulsive buying behaviour, millennials, sensory marketing were obtained from journals and publications of previous scholars both local and international. The findings of the study revealed that store environment, floor merchandising, and sales promotions significantly influence the pattern of purchasing behaviour of millennials, which triggers impulsive buying. It was recommended that marketers who focus on millennial goods and services should employ the findings of this study to increase impulse purchases. On the side of the millennials, they should familiarise themselves with different marketing strategies to critically manage their buying pattern.